2012
DOI: 10.4236/ojpchem.2012.23014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Binary Oxidant (FeCl<sub>3</sub>:APS) Ratio on the Spectroscopic and Microscopic Properties of Poly(2,5-Dimethoxyaniline)

Abstract: Poly(2,5-dimethoxyaniline) (PDMA) has been synthesized by chemical oxidative polymerization technique using varying ratio (wt/wt) of binary oxidants; ferric chloride (FeCl 3 ) and ammonium persulfate (APS). Fourier transform infrared (FT-IR) and ultraviolet-visible (Uv-vis) spectroscopic investigations provide the evidence of the presence of both benzenoid and quinoid ring units. The thermal analysis and structural characterization data suggests that the oxidant ratio greatly controls the molecular ordering in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…These properties are responsible for intermolecular transport of the ionic species alongside the polymer chain and a little intermolecular hopping owing to close and better packing of the material. Consequently, this high crystallinity of the material leads to high conductivity and high electrocatalytic activity [36,37]. Literature study reveals that by using commercial phytic acid solution as a dopant, the similar behaviour of XRD pattern is obtained with low crystallinity as for other reported organic and inorganic acids doped PANI.…”
Section: Structural and Morphological Characterizationmentioning
confidence: 81%
“…These properties are responsible for intermolecular transport of the ionic species alongside the polymer chain and a little intermolecular hopping owing to close and better packing of the material. Consequently, this high crystallinity of the material leads to high conductivity and high electrocatalytic activity [36,37]. Literature study reveals that by using commercial phytic acid solution as a dopant, the similar behaviour of XRD pattern is obtained with low crystallinity as for other reported organic and inorganic acids doped PANI.…”
Section: Structural and Morphological Characterizationmentioning
confidence: 81%
“…16 The type of oxidant is a factor that most significantly affects the conductive polymer characteristics. 11,19,20 The oxidation-reduction potential of the oxidant influences the rate of polymerization, conductivity and surface morphology of polypyrrole. 21 The oxidants typically used for polypyrrole polymerization are ammonium persulfate (APS) and ferric chloride (FeCl 3 ).…”
mentioning
confidence: 99%
“…As such, binary oxidants are attracting attention in terms of addressing problems caused by single oxidants. Singh et al 20 used FeCl 3 and APS to examine the effects of binary oxidants on the appearance and electrical characteristics of poly(2,5-dimethoxyaniline) (PDMA) films. As a result, they confirmed that the benzenoid structure of PDMA was better aligned as the APS content increased, thereby increasing the crystallinity degree of polymers and improving conductivity.…”
mentioning
confidence: 99%
“…The mean particle size of CdS was calculated using scherr equation and found to be 19.57nm. The increase of crystallinity may be due to the replication of Benzenoid and Quinoid rings in PDMA [11]…”
Section: B Synthesis Of Poly (2 5-dimethoxyaniline)mentioning
confidence: 99%
“…The blend films have an absorption bands around 330nm is attributed to the π -π* transition of the benzenoid ring [11].…”
Section: Uv -Vis Spectra Analysismentioning
confidence: 99%